Enclaves, Language and the Location Choice of Migrants - Thomas K. Bauer; Gil S. Epstein; Ira N. Gang (Institute for the Study of Labor (IZA), 2002)
Empirical studies in the migration literature have shown that migration enclaves (networks) negatively affect the language proficiency of migrants. These studies, however, ignore the choice of location as a function of language skills. Using data on Mexican migration to the US, we show that migrants choose smaller networks as their English language proficiency improves.
Keywords: F22; J61; J15; 330; immigrants; language skills; enclave; networks; ethnic goods; ethnic concentration; Migranten; Sprache; Englisch; Ethnische Gruppe; Mexikaner; Netzwerk; Wohnstandort; Vereinigte Staaten